Genetic survey of caribou populations using microsatellite DNA - Kushny, James E.E.; Coffin, John W.; Strobeck, Curtis (Rangifer, 1996)
Microsatellite loci are highly variable regions of eukaryotic DNA that consist of tandemly repeated sequences of one to six nucleotides in length. The use of microsatellites and the Polymerase Chain Reaction (PCR) are powerful tools for quantifying genetic variation within and among individual populations. Recently, we have developed primers for caribou that amplify 4 microsatellite loci. These microsatellite loci were used to survey the genetic variation in populations of Barren-ground caribou (Rangifer tarandus groenlandicus), Peary caribou (R.t. pearyi) and Woodland caribou (R.t. caribou) of Canada. The four loci examined were all polymorphic, revealing high levels of heterozygosity (> 0.74) in all of the study populations.